The regulatory activities of MALAT1 in the development of bone and cartilage diseases - Zhang, Di; Xue, Jinhua; Peng, Fang (Frontiers in Endocrinology, 2022)
Long non-coding RNAs (lncRNAs) have been comprehensively implicated in various cellular functions by mediating transcriptional or post-transcriptional activities. MALAT1 is involved in the differentiation, proliferation, and apoptosis of multiple cell lines, including BMSCs, osteoblasts, osteoclasts, and chondrocytes. Interestingly, MALAT1 may interact with RNAs or proteins, regulating cellular processes. Recently, MALAT1 has been reported to be associated with the development of bone and cartilage diseases by orchestrating the signaling network. The involvement of MALAT1 in the pathological development of bone and cartilage diseases makes it available to be a potential biomarker for clinical diagnosis or prognosis. Although the potential mechanisms of MALAT1 in mediating the cellular processes of bone and cartilage diseases are still needed for further elucidation, MALAT1 shows great promise for drug development.